Call Me Angakkuq: Captain George Comer and the Inuit of Qatiktalik - Driscoll Engelstad, Bernadette (Études Inuit Studies, 2018)
Through many years of dedicated fieldwork in the Canadian Arctic, Captain George Comer laid a solid foundation for the future of museum anthropology. With the support of Franz Boas, Captain Comer—a New England whaling master with little formal schooling—assembled an extensive collection of Inuit ethnographic and archaeological artifacts, photographs, sound recordings, and natural history specimens for the American Museum of Natural History in New York City, as well as major museums in Berlin, Ottawa, and Philadelphia. This article examines a remarkable segment of that collection, the production of Inuit facial casts—portraits of over two hundred men, women, and children—created by Comer at Qatiktalik (Cape Fullerton), a whaling site on the west coast of Hudson Bay. In tandem with photographs taken by Comer, Geraldine Moodie, and others at the time, these facial casts comprise a vital chapter of Inuit social history, preserving the memory of individuals and families who lived, worked, and traded at Qatiktalik. Accompanied by detailed biographical documentation prepared by Captain Comer, this extraordinary collection acknowledges the significance of personhood, a key concept in modern anthropological theory, and provides meaningful insight into the early social, cultural, and political history of Nunavut in the Canadian Arctic.